The Love Life of Saint Alphonsa - Perumpallikunnel, Kurian (Asian Horizons, 2008)
In this article. Dr Perumpallikunnel. eMI makes a contemplative reflection on the life of Saint Alphonsa. the first woman saint canonized on Sunday. 12 October 2008. The article paints Saint Alphonsa as a representative of bridal mysticism in the lineage of bhaktitradition. The author argues that Saint Alphonsa was not as pathetic and miserable as some people want us to believe. but she was a great mystic who was elevated to higher levels of beatific vision.